Apigenin is an anoikis sensitizer with strong anti-metastatic properties in experimental breast cancer - Ruijie Xu; Zhijie Yao; Hao Zhang; Haitao Li; Wei Chen (Food Science and Human Wellness)
Loss of susceptibility to anoikis signals is a crucial step in metastasis. Anoikis resistance therefore represents a promising adjuvant therapeutic target for cancer management. In this study, we have conducted a rationalized screening to search for novel leading anoikis sensitizer from daily foods. Among 19 tested dietary phytochemicals, the best results were obtained with apigenin, a natural component of celery. Phenotypically, apigenin sensitized breast cancer cells to anoikis, lowered the number of circulating tumor cells, and protected against breast cancer metastasis to lung in mice. Mechanistically, we demonstrated that the thromboxane A2 (TXA2)-TXA2 receptor (TP) axis has a critical role in acquired anoikis resistance by activating PI3K-Akt signaling pathway. Blockage of TXA2 signaling up-regulated p53 as well as its target gene p21, caused a G1 phase arrest, and finally led to apoptosis in breast cancer cells. TXA2 level was positively correlated with breast cancer cell anoikis rate, and apigenin significantly inhibited TXA2 biosynthesis in vitro and in vivo. Collectively, we identified apigenin as a potent anoikis sensitizer with anti-metastatic properties in a mouse model of breast cancer, and these findings might provide a rationale for introducing apigenin supplementation to breast cancer patients.